The Survey on Scientific Reasoning Skill of Pre-Service Elementary Teacher in Indonesia - Fatimah, Siti; Sarwi, Sarwi; Linuwih, Suharto; Dewi, Novi Ratna (Universitas Negeri Semarang, 2025)
Scientific reasoning skills are a crucial competency to be developed in 21st-century education. This research aims to analyze the profile of pre-service elementary teachers' scientific reasoning skills. This study employs a survey conducted on students in public and private universities in Indonesia. The data collection technique utilizes a three-tier multiple-choice test. The data analysis technique is descriptive. The results of the analysis indicate that the scientific reasoning skills of pre-service elementary teachers are in the low category, with their level of confidence in solving the problems also being low. These findings imply the necessity of developing scientific reasoning skills as an effort to enhance the higher-order thinking skills of pre-service elementary teachers.